23 The Implementation of a Hospital "Buddy Walking Programme" to Improve Access to Mobility for Acute Hospital in-Patients. (16th September 2019) - Lombard, Eileen; Higgins, Anna; Timmons, Suzanne; McCullagh, Ruth
Abstract: Background: An acute hospital admission often means that patient's mobility can decline if not maintained and encouraged throughout their inpatient stay. The "Buddy Walking Programme" is a joint initiative between the physiotherapy department, nursing department and hospital volunteers. The aim of this research was to implement a hospital "Buddy Walking Programme" within a teaching hospital in Cork to allow the provision of accompanied walking sessions by members of the hospital's volunteer team. Methods: Ward based physiotherapy staff and nursing staff identify suitable patients and add their bed number and mobility status to a list each morning. Patients are identified who are independently mobile or can safely mobilise with the supervision of one person, with or without a mobility aid and who are cognitively capable of simple commands. Physiotherapists and nursing staff are made aware of the programme at induction. Volunteers partake in an educational session and manual handling training prior to offering supervised walking sessions. Results: A standard operating procedure has been developed for the "Buddy Walking Programme". Training has been rolled out hospital wide amongst nursing staff, physiotherapy staff and hospital volunteers. Conclusion: This programme will help encourage a culture of physical activity within the hospital in-patient setting and improve mobility levels. Further research is warranted to explore the beliefs and perceptions of hospital staff and volunteers regarding the initiative and to examine barriers and facilitators to the programme.